Rancang Bangun Game Edukasi Pembelajaran Bahasa Daerah Bolaang Mongondow Berbasis Android - Sugeha, Moh. Sidik; zohrahayaty; Yasin Aril Mustofa; Abd Rahmat karim Haba (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2024)
Abstract - Local languages are often endangered due to lack of use and maintenance. By learning local languages from an early age, students can maintain and develop the local language of Bolaang Mongondow to obtain the results of making an interesting educational game of the local language of Bolaang Mongondow in increasing elementary school students' interest in learning. Students often feel bored and uninterested when learning local languages due to the lack of interesting and interactive learning methods. With the existence of an interesting and interactive local language learning of Bolaang Mongondow, this educational game can be an effective tool to increase student interest in learning local languages. The educational game design has two main menus, namely the learning menu and the playing menu. In the learning feature, players can learn the vocabulary contained in the Bolaang Mongondow language educational game. While in the playing menu, players will choose the game level in which at each level, the player will play by dragging letters to the letter box until they are arranged correctly. The results of black box testing show that the Bolaang Mongondow Language educational game can run well without any errors in the features contained in the game. The results obtained in user acceptance testing show that the Bolaang Mongondow Language educational game can be accepted by students with a total score of 95% which can be categorized as Very Feasible. Keywords: Local Language of Bolaang Mongondow, Educational Game, Android